Critical Analysis of The Republic of Indonesia Police in The Implementation of Cybercrime Law in Indonesia - Yaris Adhial Fajrin; Muh. Fadli Faisal Rasyid; Grenaldo Ginting; Eka Ari Endrawati; Viorizza Suciani Putri (Journal Equity of Law and Governance, 2024)
The purpose of this research, which is based on an evaluation of Indonesia's cybercrime legislation, is to examine the difficulties encountered by the Indonesian National Police in carrying out their duties to combat cybercrime and computer crime, and to draw conclusions about how recent technological advancements have contributed to an increase in both the frequency and severity of these crimes. This study employs a philosophical and analytical approach to normative law as its research methodology. It examines applicable statutes and regulations, as well as legal theory and current practices in law enforcement. Cybercrime is on the rise, and the study's findings suggest that this trend is directly tied to the expansion of information technology, which in turn allows cybercriminals to employ more complex strategies. Not having clear legislative restrictions pertaining to cybercrime, insufficient preparation on the part of law enforcement, subpar system security, and an uninformed public are the primary challenges. Some of the proposals include creating communication platforms amongst law enforcement agencies to boost collaboration in the fight against cybercrime, educating the public and conducting targeted investigations using cutting-edge technical methods, and expanding outreach and education efforts to the general population.